Foreign policy of Central Asian countries and issues of international security - Azis Isaev; Almas Ashiraliev; Dolon Maldybaev (Clío, 2025)
The study aimed to identify the key factors shaping the foreign policy course of the Kyrgyz Republic and their impact on regional security in Central Asia. The research was based on a comprehensive analysis of international treaties, strategic documents, and analytical materials, employing systemic, comparative, and structural-functional methods, as well as statistical analysis of economic indicators. The study established that Kyrgyz Republic foreign policy has undergone a significant transformation, reflecting profound changes in the region’s international relations system. The main trends in the evolution of the country’s foreign policy course have been identified: increasing centralisation in defining international strategy, expanding the geography of foreign economic relations, and deepening multilateral cooperation. It was determined that the implementation of large-scale infrastructure projects with international partners has strengthened the country’s transit potential but has also led to a significant increase in external debt. The study demonstrated that the development of relations with new international partners, confirmed by the signing of several strategic agreements, has expanded the scope for foreign policy manoeuvring and strengthened the country’s position on the international stage.